Development of High Gain Circularly Polarized Antenna Array for RF Renewable Energy - Chao Kang, Chia; Ayuni, Fatin; Yang Kang, Chia (International Journal of Engineering and Technology, 2018)
RF energy has become very attractive in the engineering and scientist field for green substainbility. A novel high gain circularly polarize antenna array for RF renewable energy is presented in this paper. The antenna structure was investigated using full wave electromagnetic field analysis. Finally, the entire structure of the antenna array was fabricated and measured. A comparison between simulated and measured results has been observed. The results show that high gain 5.0dBi at 956MHz had been achieved for circularly polarize antenna array and the works concludes that the investigation of high gain antenna system was successful and it can use as an alternatif sources for renewable green energy. The antenna structure that presented is also an important part of the IoT and 5G development.